Global impacts of a Foreshock Bubble: Magnetosheath, magnetopause and ground-based observations - Archer,MO; Turner,DL; Eastwood,JP; Schwartz,SJ; Horbury,TS (Planetary and Space Science, 2014)
Using multipoint observations we show, for the first time, that Foreshock Bubbles (FBs) have a global impact on Earths magnetosphere. We show that an FB, a transient kinetic phenomenon due to the interaction of backstreaming suprathermal ions with a discontinuity, modifies the total pressure upstream of the bow shock showing a decrease within the FBs core and sheath regions. Magnetosheath plasma is accelerated towards the intersection of the FBs current sheet with the bow shock resulting in fast, sunward, flows as well as outward motion of the magnetopause. Ground-based magnetometers also show signatures of this magnetopause motion simultaneously across at least 7 h of magnetic local time, corresponding to a distance of 21.5RE transverse to the Sun–Earth line along the magnetopause. These observed global impacts of the FB are in agreement with previous simulations and in stark contrast to the known localised, smaller scale effects of Hot Flow Anomalies (HFAs).